The linguistic miracle of the Qur’an is fraught with ambiguity and ambiguity - Khawla Aziz Rashid; Muhammad Aziz Ali (Islamic Sciences Journal, 2024)
ABSTRACT The most preoccupied of our scholars from the Qur’an is: the secret of its inimitability, that secret that minds have wandered about in revealing, and in its description the kernels got lost, until it was inherited from generation after generation, and when they reached it, their sects varied and their paths varied, so they said of linguistic miracles, historical, medical, scientific, and metaphysical And the Psychological One and others, all of whom have inferred from the Qur’an what he went to, but what the scholars favored regarding the issue of the miraculous, is its occurrence in terms of eloquence and eloquence. And researchers, in order to reveal the secrets of his miraculousness, and no one knows his secret.